Uso de redes mesh como solução para o canal de retorno da TV digital interativa - Ribeiro, Anna Verônica Fernandes (2007)
This dissertation proposes the use of wireless ad hoc networks as a solution for the interactivity channel of the Brazilian Digital TV System in geographical areas where no cabling infrastructure exists, e.g. underprivileged communities in big Brazilian cities. It analyzes the background information of this scenario as well as explores and compares some routing protocols for ad hoc networks through simulations with the Network Simulator software (NS-2).